Rural School Funding Inequities: An Analysis of Legal, Political, and Fiscal Issues - John Dayton (Journal of Research in Rural Education, 1998)
There is a long history ofinequitable and inadequatefundingfor rural schools and difficult legal, political, andfiscal issues associated with efforts to resolve this dilemma. This article examines school funding equity litigation concerning rural schools, the effects ofpolitical power on rural funding, rural and urban competitionforfunding, the unique funding problems ofrural schools, the growing threat to equity posed by sales taxfunding schemes, andfuturefunding litigation strategiesfor rural schools. Since Serrano v. Priest (1971), 17 federal and state supreme court opinions have discussed the unique concerns ofrural schools infunding cases, with 11 ofthese opinions occurring since 1993. Many ofthese more recent cases prominently illustrate what may be an escalating legal battle over financial resources between rural and metropolitan area schools. In this struggle for resources, metropolitan area schools enjoy significant political andfiscal advantages over rural schools, limiting remedial options for rural schools. Absent adequate political orfiscal remedies for rural school funding problems, litigation may be the only remaining option for obtaining reliefin some states.